SUGGESTIONS FOR THE CONTENT OF CORPORATE REPORTS. - Eisenstein, Alex (The Accounting Review, 1941)
The past few years have given birth to a remarkably increased attention to the form and content of corporate reports to stockholders. Despite the interest in this area, very little research has been inaugurated to determine exactly what type of information stock holders desire. In a general way everyone knows that a stockholder wants the financial statements i.e. balance sheet and profit-and-loss statement. Beyond this, however, is a vast unexplored, uncharted wilderness. The additional information contained in the annual reports has ranged from absolutely no additional information to reports containing hundreds of pages of supplementary data. The annual reports of the Diamond Match Co., for example, range from 150 to 250 pages each year. This research was undertaken with a dual objective. First, to determine what information the investor desired in an annual report of a corporation and secondly, to formulate a "check-list" based upon the results of such a survey which might act as a guide to officers and direction in their yearly task of reporting to the stockholders.